Intolerance of uncertainty, rumination, post-traumatic stress symptoms and aggression during COVID-19: a serial mediation model - Celik, Dilek; Alpay, Emre H.; Celebi, Betul; Turkali, Aras (Taylor & Francis Ltd, 2021)
Background The coronavirus disease 2019 (COVID-19) pandemic can be identified as a source of traumatic stress. Previous studies have shown that post-traumatic stress and intolerance of uncertainty are associated with aggressive behaviour. Objective In the present study, we aimed to test a serial mediation model, considering rumination and post-traumatic stress symptoms (PTSS) as mediators that link intolerance of uncertainty and aggression, while controlling the confounding effect of crisis-induced health and socioeconomic stressors during the COVID-19 pandemic. Method A total of 714 participants [533 (74.6%) females, 176 (24.7%) males, aged 18-64 years (M (age) = 25.16, SD (age) = 9.34)] completed the following self-reported scales: Aggression Scale, COVID-19 stressors checklist, Short Version of the Intolerance of Uncertainty Scale, Impact of Event Scale with Modifications for COVID-19, and Ruminative Thought Style Questionnaire. Results The results revealed that there was an association between intolerance of uncertainty and aggressive behaviours. Moreover, the results of serial mediation analysis showed that intolerance of uncertainty predicts aggressive behaviours via rumination and PTSS. Besides, socioeconomic stressors are significantly associated with the level of PTSS and aggression, while health stressors are not significantly association with the level of PTSS and aggression. Conclusions The findings provide several contributions to understand the link between intolerance of uncertainty and aggressive behaviours during the COVID-19 pandemic, and confirm the importance of early psychological intervention, especially for those who are more likely to ruminate and suffer from PTSS, to prevent aggression and violence in the long run. In addition to health-related regulations, it is important to take the social and economic aspects of the crisis into account and develop intervention strategies accordingly. Nevertheless, the limitations of cross-sectional mediation analysis in explaining causal relationships should be kept in mind, and future studies should extend these findings using longitudinal data.
Keywords: Rumination; intolerance of uncertainty; aggression; post-traumatic stress symptoms; COVID-19